Drop-off detection with the long cane: effect of cane shaft weight and rigidity on performance. Issue 1 (2nd January 2017) - Kim, Dae Shik; Wall Emerson, Robert; Naghshineh, Koorosh; Auer, Alexander
Abstract: Most travellers who are blind rely on a long cane to detect drop-offs on their walking paths. We examined how different cane shaft materials affect drop-off detection performance through providing different vibrotactile and proprioceptive feedbacks to the cane user. Results of the study showed a significant interaction between cane shaft weight and how the cane is used. A heavier cane was advantageous for detecting drop-offs when the individual used the 'constant contact technique' – cane tip stays in contact with the walking surface at all times – but not when he used the 'two-point touch technique' – cane tip is rhythmically tapped on the surface. In addition, a more flexible cane was advantageous for detecting drop-offs when the two-point touch technique was used but not when the constant contact technique was used. It is recommended that, when blind individuals select a cane shaft material, they consider which long cane technique they use more often. Practitioner Summary : Long cane shaft material affects how well a blind individual can detect drop-offs. A heavier shaft was advantageous when using the constant contact technique (cane tip stays in continuous contact with the surface), while a more flexible shaft was better when using the two-point touch technique (cane tip rhythmically taps the surface).